Attending to the spiritual through the teaching of science: a study of pre‐service primary teachers’ attitudes - Stolberg, Tonie L. (International journal of children's spirituality, 2008)
Analysis of the attitudes of 140 pre‐service primary teachers, and of extended interviews with 15 of these prospective teachers, indicates differences in the ways pre‐service teachers use science in their heuristic reasoning and their ability and/or willingness to include a spiritual dimension in their science teaching. These differences were a reflection of neither the prospective teachers’ formal scientific training nor their personal religious faiths – both factors have been found to make little difference. Rather, they are indicative of how their personal conceptual frameworks emanate and influence their teaching approaches. Most are clearly able to engage with science’s spiritual component: an appreciation of the need for individual humility and recognition that scientific understanding is the result of a shared, collective endeavour. Despite most prospective teachers being neither hostile to the thought of addressing spiritual issues during their teaching of science nor totally convinced of its importance, they are also largely ignorant of the possibility, never mind the potential benefits, of its inclusion.